Mathematical modeling mechanisms of arrhythmias in transgenic mouse heart overexpressing TNF-α - Petkova-Kirova, Polina S. (American Physiological Society, 2012)
Transgenic mice overexpressing tumor necrosis factor-α (TNF-α mice) possess many of the features of human heart failure, such as dilated cardiomyopathy, impaired Ca(2+) handling, arrhythmias, and decreased survival. Although TNF-α mice have been studied extensively with a number of experimental methods, the mechanisms of heart failure are not completely understood. We created a mathematical model that reproduced experimentally observed changes in the action potential (AP) and Ca(2+) handling of isolated TNF-α mice ventricular myocytes. To study the contribution of the differences in ion currents, AP, Ca(2+) handling, and intercellular coupling to the development of arrhythmias in TNF-α mice, we further created several multicellular model tissues with combinations of wild-type (WT)/reduced gap junction conductance, WT/prolonged AP, and WT/decreased Na(+) current (I(Na)) amplitude. All model tissues were examined for susceptibility to Ca(2+) alternans, AP propagation block, and reentry. Our modeling results demonstrated that, similar to experimental data in TNF-α mice, Ca(2+) alternans in TNF-α tissues developed at longer basic cycle lengths. The greater susceptibility to Ca(2+) alternans was attributed to the prolonged AP, resulting in larger inactivation of I(Na), and to the decreased SR Ca(2+) uptake and corresponding smaller SR Ca(2+) load. Simulations demonstrated that AP prolongation induces an increased susceptibility to AP propagation block. Programmed stimulation of the model tissues with a premature impulse showed that reduced gap junction conduction increased the vulnerable window for initiation reentry, supporting the idea that reduced intercellular coupling is the major factor for reentrant arrhythmias in TNF-α mice.